The Use of AI in Education to Improve Elementary School Students' Learning Outcomes - Agustinus Sembiring; Theresia Herlina (Indonesian Journal of Advanced Research, 2026)
This study examines the impact of Artificial Intelligence (AI) on learning quality in elementary schools with limited technology infrastructure. Addressing unequal AI adoption, a quasi-experimental design was applied to 130 fifth-grade students divided into AI-based and conventional groups. Data were collected through pretest–posttest and EKOP questionnaires, analyzed using t-tests and reliability measures. Results show the AI group improved from a mean pretest score of 56.65 to 78.85 (gain = 22.20), while the non-AI group increased from 57.15 to 67.60 (gain = 10.45), with significant differences (t = 15.15, p < 0.001). EKOP scores also favored the AI group across all indicators. This study contributes empirical evidence that AI enhances engagement, critical thinking, and learning outcomes in rural elementary contexts.